Risk Factors for Acute Respiratory Infections in Underfive Children - Cissy B. Kartasasmita; Maurits Demedts (Indonesian Pediatric Society, 1995)
A longitudinal study on acute inspiratory infections was conducted from April 1988 until June 1990, in Cikutra, an urban community in the municipality of Bandung, Indonesia. The study consisted of. 3 parts: a presurvey, a cross sectional study, and a one-year prospective study. All children aged less than five years in Cikutra were included in the presurvey. A simple questionnaire was used for collecting data. In the cross sectional study 500 children were selected by stratified random sampling. Field investigators visited the children's homes and interviewed mothers using a standardized questionnaire. For the prospective study 269 children of less than 48 months of age were enrolled, and followed for one year. The prevalence of all ARI was 57-58%, mild-moderate ARl 55-56% , and severe ARJ 5%. On average the children suffered from 6.7 episodes of ARl per child per year, with a mean duration of episode of 5.3 days. Several factors showed significant relationship with the prevalence, incidence, severity of duration of ARI.